Co-occurrence patterns between plant-parasitic nematodes and arbuscular mycorrhizal fungi are driven by environmental factors - Ferreira, Bruno S.; Santana, Marcus V.; Macedo, Renan S.; Silva, Juliana O.; Carneiro, Marco A.C.; Rocha, Mara R. (Agriculture, ecosystems & environment, 2018)
•Negative correlation was found between nematodes and AMF spore abundance.•Helicotylenchus did not co-occur with Rhizophagus intraradices and Glomus sp.•Potassium, phosphorus and moisture were associated with negative co-occurrence. The relationships between co-occurrence patterns of plant-parasitic nematodes and arbuscular mycorrhizal fungus (AMFs) are not fully understood. Few field studies assess co-occurrence patterns, evidencing the lack of information on soil-limiting conditions for favorable management of AMFs. The aim was therefore to evaluate co-occurrence patterns between plant-parasitic nematodes and AMFs and the probable environmental conditions that were associated to these patterns. We sampled three sites in each of ten fields and collected an abundance of nematodes and AMF spores and physical-chemical soil data. We evaluated co-occurrence patterns using combinations between nematodes and AMFs in both samplings (soil and roots) through probabilistic models. We also performed a redundancy analysis to evaluate which environmental variables were correlated to negative and positive patterns found between both groups. Plant-parasitic nematodes and AMFs showed negative co-occurrence patterns on the root-rhizospheric soil interface as a result of the competition. In the soil, the groups showed an apparent differentiation of niche, and the competition occurs within each group. Soil variation, mainly on alterations of potassium, phosphorus and moisture are the main characteristics that are associated to changes in the assemblages of these groups. Co-occurrence patterns indicated in the present study show an important pathway to conservative management of the soil and improvement of the crop growth in agricultural landscapes.